Digitalization and e‐government in the lives of urban migrants: Evidence from Bogotá. Issue 2 (10th December 2021) - Martin‐Shields, Charles P.; Camacho, Sonia; Taborda, Rodrigo; Ruhe, Constantin
Abstract: Research on the role of information and communication technologies (ICT) to improve the lives of migrants is a growing field. However, studies in this area have been conducted mainly in wealthy countries, with municipalities that are capable of supporting migrants or refugees. There is less evidence from middle‐income host countries and how ICTs can help migrants in their resettlement efforts. To address this gap, this study examines ICT access and the use of e‐government services by Venezuelan migrants in Colombia and compares this group with short‐ and long‐term residents of Bogotá. The descriptive analysis of the data reveals that, after controlling for demographic and socioeconomic characteristics, foreign migrants are less likely to own ICT devices compared to short‐ and long‐term residents, but over time do acquire ICT access. In addition, Venezuelan migrants are less likely to use e‐government services than their local peers even after controlling for demographic characteristics and internet access, with the exception of address registration. The results indicate that ICT access is not a sufficient condition for migrants to access e‐government services and there is a need for policy coordination to reduce bureaucratic "red tape" that may diminish migrants' likelihood of accessing to e‐government services.